2019
DOI: 10.1093/jrr/rrz066
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of treatment strategy by using a machine learning model to predict survival time of patients with malignant glioma after radiotherapy

Abstract: ABSTRACT The purpose of this study was to predict the survival time of patients with malignant glioma after radiotherapy with high accuracy by considering additional clinical factors and optimize the prescription dose and treatment duration for individual patient by using a machine learning model. A total of 35 patients with malignant glioma were included in this study. The candidate features included 12 clinical features and 192 dose–volume histogram (DVH) featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Mizutani et al employed scans of 35 patients with malignant glioma, identifying 12 clinical features and 192 dose-volume histogram (DVH) features and used SVM to predict OS times after RT. They found that prediction accuracy was significantly improved with the combined use of clinical and DVH features compared with the separate use of each feature (66). Qiu et al compared RSF and traditional CPH to predict tumor progression after particle beam radiotherapy in 82 HGG patients and found that CPH demonstrated a better performance in terms of integrated C-index as compared to the RSF model (18).…”
Section: Imaging and Response To Treatmentmentioning
confidence: 99%
“…Mizutani et al employed scans of 35 patients with malignant glioma, identifying 12 clinical features and 192 dose-volume histogram (DVH) features and used SVM to predict OS times after RT. They found that prediction accuracy was significantly improved with the combined use of clinical and DVH features compared with the separate use of each feature (66). Qiu et al compared RSF and traditional CPH to predict tumor progression after particle beam radiotherapy in 82 HGG patients and found that CPH demonstrated a better performance in terms of integrated C-index as compared to the RSF model (18).…”
Section: Imaging and Response To Treatmentmentioning
confidence: 99%
“…Machine learning (ML), a branch of artificial intelligence, has been employed to predict prognosis in a variety of cancer types. Noticeably, series of studies applying ML algorithms to predict the survival of HGG under standard photon-based radiotherapy have reported good performance in recent years (8)(9)(10)(11)(12)(13). However, it is still controversial that which methods among ML algorithms and conventional modeling can achieve better performance in survival analysis, particularly in terms of time-to-event censored data (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…First, there are many reports on the survival analysis of patients with HGG based on clinicopathological factors and data mining of imaging variables. However, only a limited number of studies have investigated the importance of DVH for survival 36 . In this study, clinical and DVH features were combined to construct a prognostic prediction model, and we found that radiation dose information can affect prognosis.…”
Section: Discussionmentioning
confidence: 93%